Editorial - Jörg Tremmel; Markus Rutsche (Intergenerational Justice Review)
While the unprecedented lockdown measures were at the heart of the debate in the first year of the pandemic, the focus since then has shifted to vaccination issues. The reason, of course, is that vaccines and vaccinations have become available by now. All experts agree: If mankind had failed to develop vaccines against SARS-CoV-2, the death toll would have been much higher. This issue seeks to explore what could be described as a “generational approach to vaccinations”. The question “What can we do to avoid future pandemics?” is related to different aspects of the failures and successes of humanity’s vaccination strategy against SARS-CoV-2.